Iatrogenic pyriform sinus perforation during endoscopic ultrasonography - Young Min Kim; Jae Jun Park; Young Hoon Youn (Society of Gastrointestinal Intervention, 2019)
Summary of Event A 65-year-old women underwent endoscopic ultrasonography (EUS) to evaluate the gastric submucosal tumor. The EUS scope was inserted into the esophagus after two attempts. A neck computed tomography (CT) scan showed a pneumomediastinum and an air bubble deep in the neck, suggesting an esophageal rupture. The patient was hospitalized and maintained conservative treatment including broad-spectrum antibiotics and withholding oral feeding. Teaching Point Endoscopists should consider an imaging modality when a patient complains of moderate to severe neck pain after an upper endoscopy. Prompt surgical management should be considered in patients with a delayed diagnosis (> 24 hours), those with signs of systemic toxicity, and those who have eaten between the time of the procedure and when the perforation was detected.